2020
DOI: 10.5539/mas.v14n4p14
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Strategies Human Resource Management on Organizational Commitment. (An Applied Study on Employees in Jordanian Islamic Banks)

Abstract: The present study aimed to explore the impact of strategies human resource management (SHRM) (recruitment, training, compensation, and performance management) on organizational commitment, An applied study on employees in Jordanian Islamic banks. It was found that the strategies human resources management in Jordanian Islamic banks is high. It was found that the employees’ organizational commitment level in Jordanian Islamic banks is high. There is a statistically significant effect at the level (&am… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 7 publications
0
2
0
Order By: Relevance
“…The findings revealed that green HRM practices' successful implementation changes employee behavior to act responsible and lead to sustainable performance. Almutairi and Alsawalhah (2020) proposed a framework on the relationship between green HRM and organizational commitment in Islamic banks. Their findings recommend that green HRM strategies should be consistent with the external environment to increase environmental performance.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The findings revealed that green HRM practices' successful implementation changes employee behavior to act responsible and lead to sustainable performance. Almutairi and Alsawalhah (2020) proposed a framework on the relationship between green HRM and organizational commitment in Islamic banks. Their findings recommend that green HRM strategies should be consistent with the external environment to increase environmental performance.…”
Section: Literature Reviewmentioning
confidence: 99%
“…(Nasser & Saadeh, 2013). In addition to this, it is necessary to determine the different job sizes, in a manner consistent with the organization's mission and strategic directions, taking into account the dimensions and conditions of the competitive environment (Almutairi & Alsawalhah, 2020). This is done by determining the area of each job, the degree of its breadth or capacity, and then its workload.…”
Section: Dimensions Of Organizational Integrationmentioning
confidence: 99%